The role of information and communication technologies in achieving hydropower sustainability: evidence from European Union economies - Wang, Xiaohui; Mohd Alsaleh; Abdul-Rahim, Abdul Samad (SAGE Publications, 2024)
This study aims to investigate the impacts of information, communication, and technology (ICT) factors and economic growth on the hydropower output in the European Union (EU) states from 1990 to 2021. Adopting the autoregressive distributed lag, findings from this study revealed that there could be a significant increase in the hydropower industry growth in EU14 emerging economies using ICT factors than in EU13 emerging economies. It was also discovered that economic growth makes more of a significant contribution to hydropower growth in EU13 emerging economies than in EU14 emerging economies. Findings from this study further revealed that there could be a significant decrease in the carbon dioxide emissions among the EU14 emerged economies using hydropower output than in EU13 emerging economies. This points to the fact that hydropower growth in EU region countries could significantly be enhanced by increasing the level of ICT determinants to achieve Energy Union aims by 2030. This will as well be effective in minimizing or reducing the risk effect of climate change and environmental pollution. Using the pooled mean group, mean group, and dynamic fixed effect methods, the projected calculations are observed to be valid and this study recommended that EU nations should intensify the use of ICT in achieving sustainable environmental and societal goals. The sustainability and security of hydropower production could also be enhanced through legislation. Lawmakers should become active in the green ICT aspects.